Gradual reduction vs abrupt cessation as a smoking cessation strategy in smokers who want to quit. - Lindson-Hawley, N; Aveyard, P; Hughes, JR (2013)
CLINICAL QUESTION: Is gradual smoking cessation associated with poorer success rates than abrupt cessation in smokers who want to quit? BOTTOM LINE: Gradual reduction may not be associated with a clinically significant difference in smoking cessation rates compared with abrupt cessation.